Death of a traitor [compact disc, unabridged] - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Hamish Macbeth mystery (Sound recording), 2023)
The interfering Kate Hibbert has lived in the Highlands for only a year yet has alienated many villagers. When she disappears, constable Hamish Macbeth discovers some sinister doings.